(untitled) (Trabalho & Educação, 2016)
The present work had the aim of reflecting the relationship between the representations and the practice in the activity of low-educated workers. The demand is related to the increase of the performance of those workers, essentially the ones, who are considered less competent due to their lack of mathematical concepts knowledge. Aiming to understand what they know and the know-how of those, that are effective, we used the Activity Analysis methodology and the course of action. Workers with different performances in solving problems in work situations were researched. The theoretical discussion started from the debate occurred between the cognitive and pragmatic chains, which adopt different positions about the relation between representation and practice on the course of action. The first puts the representation as a cause of the action, while the second looks for the actor’s intrinsic point of view, putting the effectiveness in the interlacement in situation among actions, perceptions and representations. The difficulty occurred in the data analysis. The researcher tended to the cognitive side, revealing the difficulty of an analysis immanent of the activity that seeks to understand it inside of a social context, and not externally, when comparing educational and daily representations. The results showed that an effective action depends more on mastering the social practice, stronghold of specific rules and values, than on possessing mathematical representations, and that they obtain meaning inside of a social activity. __ O presente trabalho tem como objetivo refletir a relação entre as representações e a prática na atividade de trabalhadores pouco escolarizados da construção civil. A demanda é o aumento da performance desses trabalhadores, considerados pouco competentes, devido ao desconhecimento de conceitos matemáticos. Visando compreender o que sabem e como sabem aqueles considerados eficazes, foi utilizada a metodologia da Análise da Atividade. Foram analisados trabalhadores com desempenho distinto solucionando problemas em situações de trabalho. A discussão teórica partiu do debate estabelecido entre a corrente cognitivista e a da ação situada, que adotam posições distintas sobre a relação entre a representação e a prática no curso da ação. A primeira coloca a representação como causa da ação, enquanto a segunda, como recurso da ação, cuja eficácia decorre menos das representações isoladas e mais do engajamento em uma atividade prática social. O embaraço ocorreu na análise dos dados. A pesquisadora caiu no viés cognitivista, revelando a dificuldade de uma análise imanente da atividade, que buscasse compreendê-la inserida em um contexto social, e não externamente, ao comparar as representações matemáticas. Os resultados mostraram que a ação eficaz depende mais do domínio da prática social, reduto de normas e valores específicos, do que da posse de representações matemáticas e que estas ganham sentido no interior da atividade social.